IFC at an Inflection Point : Time for a New Business Delivery Model? - Zaki, Fares T. (World Bank, Washington, DC, 2014)
As International Finance Corporation (IFC) continues to further scale up its operations, seeking to deliver more development impact, could it be in danger of inadvertently becoming an increasingly slower and higher-cost delivery mechanism, and thus a less relevant change agent? This smart lesson, growing out of the author's observations during 32 years with IFC, proposes an alternative business delivery model with particular relevance to fragile states and frontier regions in middle income countries, in hopes of sparking a lively and productive debate around how IFC defines, delivers and measures success in its poverty reduction effort.